The Association Between Body Mass Index, Waist to Hip Ratio and Mid-Upper Arm Circumference with Endometriosis (Unnes Journal of Public Health, 2022)
Endometriosis is characterized by the presence of endometrial tissue, in the form of glands and stroma outside of the uterus. This study aimed to determine the relationship between body mass index, waist to hip circumference ratio, and mid-upper arm circumference with the incidence of endometriosis. This study was analytical observational research with a case-control. The subjects were 63 patients diagnosed with endometriosis through laparoscopic action and 63 normal women who both met inclusion and exclusion criteria. The measurement result of body mass index (BMI) in kg/m² is categorized into ≤25 and >25, waist to hip ratio is categorized to <0.85 and ≥0.85, mid-upper arm circumference in centimeters to ≤23.0 and >23.0. The result showed the relationship of body mass index, waist to hip ratio, and mid-upper arm circumference with endometriosis incidence obtained BMI with endometriosis (b=0.824, CI 95%=0.99 to 5.25, p=0.053), waist to hip ratio (b=0.893, CI 95%=1.03 to 5.82, p=0.044), and mid-upper arm circumference (b=-0.246, CI 95%=0.10 to 6.09, p=0.814). There is a significant relationship between BMI and waist to hip ratio with the incidence of endometriosis. There is no significant relationship between mid-upper arm circumference with the incidence of endometriosis.